Collection management basics - Evans, G. Edward, 1937-; Saponaro, Margaret Zarnosky (Santa Barbara, California : Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2012)
"Now thoroughly revised for today's 21st-century library environment, this title provides a complete update of the classic Developing Library and Information Center Collections--the standard text and authority on collection development for all types of libraries and library school students since 1979"--
Includes bibliographical references and index.
AAL
Trim Education
Keywords: Collection development (Libraries); Libraries -- Special collections -- Electronic information resources